2017
DOI: 10.1021/acs.energyfuels.7b00533
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biomass and Main Biomass Components on Coal Reactivity under Oxy-Combustion Conditions—A Comparison of Physicochemical Char Properties Obtained under N2 and CO2 Atmospheres

Abstract: In the present study, wood biomass from Acacia mangium and its main components (hemicellulose (xylan), cellulose, and lignin) were blended with a sub-bituminous coal in 20:80 wt % ratio and subsequently were heat-treated at 900 °C using CO2 or N2 atmospheres. The reactivity (ignition temperature and activation energy) under oxy-fuel conditions (21% O2–79% CO2) was studied by thermogravimetry (TGA). It has been observed that adding biomass or its main components to coal improved the combustion efficiency. Coal/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…This behavior suggests that the presence of potassium during the thermal process accelerates the cracking degree of the amorphous carbon fraction; therefore, the graphitization signal diminishes considerably. These results are in agreement with our previous work 26 .…”
Section: Raman Analysissupporting
confidence: 94%
See 3 more Smart Citations
“…This behavior suggests that the presence of potassium during the thermal process accelerates the cracking degree of the amorphous carbon fraction; therefore, the graphitization signal diminishes considerably. These results are in agreement with our previous work 26 .…”
Section: Raman Analysissupporting
confidence: 94%
“…Oxy-combustion reactivity tests were carried out in a thermogravimetric analyzer (SDT Q600-TA Instruments) following the same methodology reported in a previous work …”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kandasamy Jayaraman et al studied coal and biomass blends and they concluded that by increasing the ratio of biomass in the blends, the mass loss percentage increases, indicating the high reactivity of samples, and the activation energies were also increased by increasing biomass ratio in the blends [57]. Betancur et al studied that coal and biomass blends increased combustion efficiency [124]. Blends showed lower ignition temperatures, and activation energies were decreased in the CO 2 environment as compared to N 2 .…”
Section: Ermogravimetric Analysis Of Coal/biomassmentioning
confidence: 99%